John Donne and the Protestant Reformation: new perspectives - Papazian, Mary Arshagouni; Donne, John (Wayne State University Press, 2003)
Polemist or pastor? Donne and moderate Calvinist conformity / Daniel W. Doerksen -- Speaking openly and speaking first / Jeanne Shami -- The Augustinian Donne / Mary Arshagouni Papazian -- John Donne and Paolo Sarpi / Jeffrey Johnson -- Donne's Protestant Paradiso / Raymond-Jean Frontain -- Soldiers of one army / Paul R. Sellin -- Unmeete contraryes / Catherine Gimelli Martin -- From "Tav" to the cross / Chanita Goodblatt -- Pathopoeia and the Protestant form of Donne's devotions upon emergent occasions / Brent Nelson -- Breaking down the walls that divide / Elena Levy-Navarro -- Reforming baptism / Annette Deschner -- True purification / Maria Salenius -- Not upon a lecture, but upon a sermon / Gale H. Carrithers, Jr., and James D. Hardy, Jr